Linking Human Resource Education and the Adoption of Cutting-Edge Technologies in Livestock Industries for Sustainable Economic Growth - Nurhaliza, Nurhaliza (Politeknik Siber Cerdika Internasional, 2024)
The livestock industry plays a crucial role in food security and economic stability but faces significant challenges in adopting advanced technologies due to a shortage of skilled human resources. This study examines the impact of human resource education on technology adoption in the livestock sector, emphasizing its implications for sustainable economic growth. Using a quantitative approach, data were collected from 300 livestock professionals through a structured questionnaire assessing their educational background, technological familiarity, and the extent of technology adoption in their workplaces. Statistical analysis, including regression techniques, revealed a strong positive correlation between higher education levels and technology adoption rates. Results showed that individuals with advanced degrees exhibited greater technological familiarity and a higher willingness to integrate innovative practices than their less-educated counterparts. These findings highlight the need for targeted educational programs to bridge the skill gap, accelerate technology adoption, and enhance sectoral efficiency. The study provides valuable insights for policymakers and industry stakeholders in designing effective training initiatives that align human resource development with technological advancements, ultimately fostering sustainable practices and economic resilience in the livestock industry.